2016
DOI: 10.1021/acs.jpcc.6b09729
|View full text |Cite
|
Sign up to set email alerts
|

A Reactive Force Field Study on the Interaction of Lubricant with Diamond-Like Carbon Structures

Abstract: We studied the degradation of a perfluoropolyether lubricant, i.e., D4OH, in the presence of different components present in hard disks including diamond-like carbon (DLC), using ReaxFF reactive force field based molecular dynamics simulations. To generate the DLC structure, a carbon-diamond structure was melted in an Ar-filled head space box at 7500 K, and was slowly cooled down to 3000 K. Then, a constant pressure (NPT) simulation was performed to adjust the sample volume and reduce the internal stress. Simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Compared with the density functional theory (DFT) and reactive coarse-grained MD, , reactive MD with ReaxFF force fields is a cost-effective and accurate method providing atomistic-level details of dynamics of systems including chemical reactions, typically more than five orders of magnitude less costly than DFT calculations . Performing ReaxFF MD simulations, Lotfi et al studied the decomposition of polar PFPE D-4OH at elevated temperatures on diamond-like carbon (DLC) surfaces and in the presence of oxygen, water, and nanoparticles of SiO 2 , FeO­(OH), and Fe 2 O 3 . Their simulation results indicated that the PFPE decomposition is accelerated by DLC, water, and the oxide nanoparticles, whereas the effect of oxygen molecules is less significant.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…Compared with the density functional theory (DFT) and reactive coarse-grained MD, , reactive MD with ReaxFF force fields is a cost-effective and accurate method providing atomistic-level details of dynamics of systems including chemical reactions, typically more than five orders of magnitude less costly than DFT calculations . Performing ReaxFF MD simulations, Lotfi et al studied the decomposition of polar PFPE D-4OH at elevated temperatures on diamond-like carbon (DLC) surfaces and in the presence of oxygen, water, and nanoparticles of SiO 2 , FeO­(OH), and Fe 2 O 3 . Their simulation results indicated that the PFPE decomposition is accelerated by DLC, water, and the oxide nanoparticles, whereas the effect of oxygen molecules is less significant.…”
Section: Introductionsupporting
confidence: 68%
“…33 Performing ReaxFF MD simulations, Lotfi et al studied the decomposition of polar PFPE D-4OH at elevated temperatures on diamondlike carbon (DLC) surfaces 15 and in the presence of oxygen, water, and nanoparticles of SiO 2 , FeO(OH), and Fe 2 O 3 . 26 Their simulation results indicated that the PFPE decomposition is accelerated by DLC, water, and the oxide nanoparticles, whereas the effect of oxygen molecules is less significant.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, they also tested the stick-slip phenomenon when the prove tip was slipped over the graphite and mica surface. Since then, numerous studies [16][17][18] have distinguished the characteristics of microtribology from macrofriction. Nonetheless, the microtribology mechanism remains poorly understood.…”
Section: State Of the Artmentioning
confidence: 99%